SOCIAL MEDIA MARKETING OF BEAUTY PRODUCTS ON INSTAGRAM ACCOUNTS @FACETOLOGYOFFICIAL - Ningsih, Putri Kuswanti; Aestetika, Nur Maghfirah (Journal of Geography, Regional Planning and Development, 2024)
General Background: Social media marketing has revolutionized the way businesses connect with customers, offering a powerful platform for promoting products and building brand awareness. Specific Background: This research focuses on the Instagram account @facetologyofficial, exploring how Facetology employs social media marketing strategies to engage consumers and drive sales. Knowledge Gap: Despite the increasing reliance on social media for marketing, there is limited research that specifically analyzes the application of social media marketing theories within local beauty brands on platforms like Instagram. Aims: The study aims to investigate the social media marketing strategies utilized by Facetology on Instagram, with a focus on their implementation of the 4Cs framework: context, communication, collaboration, and connection. Results: Employing a descriptive qualitative approach and observational data collection, the findings reveal that Facetology effectively applies the 4Cs: 1) Context—maintaining a consistent visual aesthetic across posts; 2) Communication—using photos and videos, particularly Instagram Stories for product reviews; 3) Collaboration—partnering with influencers for endorsements to enhance market reach and consumer trust; and 4) Connection—fostering customer relationships through active engagement in comments, direct messages, and sharing customer testimonials. Novelty: This study contributes to the understanding of how local beauty brands can leverage specific social media marketing strategies to enhance their online presence and customer engagement. Implications: The results highlight the importance of a structured social media marketing approach, suggesting that other businesses can benefit from implementing similar strategies to strengthen customer relationships and increase brand loyalty. This research provides practical insights for practitioners in the beauty industry aiming to optimize their social media marketing efforts.